Teatralne role Edith Piaf - Mieczysław Gajos (Pamiętnik Teatralny, 2016)
This article presents Edith Piaf not only as one of the greatest icons of French culture in the 20th century, but also as a theatrical and film actress who had dramas and movie scenarios written specifically for her. Her acting accomplishments are impressive, even though in the minds of her fans she is still associated mostly with her singing career. The article aims at presenting Edith Piaf as a theatre actress. The productions in which Edit Piaf performed as an actress are presented from a diachronic and analytical perspective. Not only the plays written especially for Piaf by dramaturge Jean Cocteau and librettist Marcel Achard, in which she performed on stage, but also radio dramas in which she played have been taken into account. In addition, the study discusses the opinions about Piaf’s acting artistry, including those published in the French press.